Gestión de riesgos mayores en las instalaciones de la Empresa Pública EP-EMMPA: plan de contingencia - Ortega Sánchez, Faride Makarena (2021)
This research project was carried out in the Public Company Mercado de Produtores Agrícolas ¨San Pedro de Riobamba¨ to manage significant risks in its administrative facilities, preparing and proposing a Contingency Plan allows the correct action of personnel in an emergency. The research design was a non-experimental, descriptive, and exploratory type. The population is 30 workers between men and women. Fires, earthquakes, and volcanic eruptions were identified and assessed as significant risks through the application of checklists and the Hazard and risk identification Matrix of Instituto Nacional de Seguridad y Salud en el Trabajo. In assessing these risks, methods such as The National Fire Protection Association NFPA, where a low risk was obtained in the administrative area; with the Simplified Method of Fire Risk Assessment, MESERI resulted in a Medium risk. Concerning the Method of Preparation and Implementation of Emergency Plans for MEIPEE companies, a medium risk level for fires, earthquakes, and volcanic eruptions was evidenced. In addition, in the FEMA 154 method, the administrative building has a low vulnerability to an earthquake. With the evaluation carried out, the Contingency Plan was elaborated according to the requirements of the Risk Management Department of the GADMRIOBAMBA. Finally, was proposed and socialized, complying with the respective processes for validation.